Analysis of mental burden of students based on NASA-TLX at DAYAH DMA - Fatimah; Subhan A. Gani; Asrar Rahmati; Syamsul Bahri (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
One of the organizations in Aceh that deals with religious instruction and learning is Dayah DMA. Students who pursue higher education and are enrolled in religious education institutions are known as mahasantri, and they are thought to possess greater physical and psychological development than students in regular schools. No doubt learning in two distinct locations has different job demands, which could put more strain on Mahasantri's mind. This study aims to determine the causes of high mental load on mahasantri and investigate potential disparities in mental burden according to gender, status, and class levels. Purposive sampling is used in this study to handle primary data from 56 mahasantri respondents who completed questionnaires as part of a quantitative approach. According to the research that was done, 50% of mahasantri, or 28, report having a significant level of mental strain. Physical demand has the highest impact on mahasantri's mental burden, accounting for 18.35% of the total. Subsequently, an independent sample t-test conducted with SPSS version 26 was employed to statistically evaluate the average mental burden score to ascertain whether mental burden varied according to gender, status, and class level categories. The burden for gender and status categories did not differ, according to the results. But in terms of mental load, there was a notable variation for the class level category